The cultural identity of white Afrikaner women: a post- Jungian perspective - Griessel, Loura; Kotzé, Martina (Acta Academica: Critical views on society, culture and politics, 2010)
A post-Jungian model of the development of the self (Hill 1992) is used to analyse how the female Afrikaner identity became embedded in the South African social and political contexts. It is argued with Jungian concepts that, because of their history and culture, Afrikaner women grew up amid a cultural identity that became entrenched in the static Masculine and a patrivalent culture pattern. Consequently, for most of the twentieth century, Afrikaner women as a group were prone to function as Father’s Daughters, with a strong constellation of the archetypal image of Amazon and its patterns of Martyr and Dutiful Daughter. Some implications for the development of the self in these women are then discussed.